Pengaruh Orientasi Kewirausahaan, Orientasi Pasar, dan Inovasi Produk Terhadap Keunggulan Bersaing Pada Usaha Kuliner Angkringan di Kesawan City Walk Medan - Abadi, Tri Ayu; Siregar, Muhammad Yamin (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study's goal is to ascertain “The Effect of Entrepreneurial Orientation, Market Orientation, and Product Innovation on Competitive Advantage in Angkringan Culinary Businesses in Kesawan City Walk Medan”. This research was prepared using causal associative quantitative methods with a population of 116 respondents and a sample of 90 respondents who were angkringan business actors at Kesawan City Walk Medan. The sampling method employed in this study was purposive sampling. Data was collected through the direct distribution of questionnaires and subsequently analyzed using SPSS to derive the research results. The study's conclusions show that competitive advantage is positively and significantly impacted by both market orientation and product innovation. Furthermore, the study demonstrates that product innovation, market orientation, and entrepreneurial orientation all favorably and significantly impact competitive advantage. Moreover, the coefficient of determination (R2) test yielded a value of 0.327, or 30.3%. This describes that the value of variance owned by the Competitive Advantage of the Entrepreneurial Orientation, Market Orientation, and Product Innovation variables is 30.3% and the remaining 69.7% is influenced by other variables or factors not explored and not addressed in this study.